Paid Academic Writing Services: A Perceptional Study of Business Students - Samiullah Sarwar; Zaeemah Muhammad Idris; Sheikh Muhammad Ali (Institute of Business Management, 2018)
It seems challenging to detect the beneficiary students of the Academic Paid Writing Services, which refers to a practice in which authors or students appoint professional writers to produce scholarly work (including research papers,  university assignments, research reports, and so on)  with a predefined style. This study aimed to explore the factors leading the students in higher education to choose the paid Academic Writing Services (PAWS), which affects their performance and personal development due to contract cheating and make them realize that learning is better than grades as through self-explorations only a person can get something better. By employing quantitative approach to obtain information associated with PAWS, data was gathered from 117 business students enrolled in six Higher Education Institutes in Karachi, Pakistan, using adopted questionnaire having close-ended questions with 5-point Likert scale, measuring students' attitude towards class assignments, their awareness about plagiarism, and their attitude about academic paid writing services. The results revealed that male students were more inclined towards paid writing services than their counterpart female students were and the increase in Students' Attitude towards Assignments brought the increase academic paid writing services. Therefore, academic professionals servicing in universities are recommended to take due care of the two factors to prevent the increased paid academic wiring services.